Search Engine of Subject Using Error Correction Lavenshtein (Case Study Digital Documents of Al Qu'ran and Hadith) - Edy Santoso; marji Marji; Nurul Hidayat (Fakultas MIPA Universitas Brawijaya, 2014)
Qur'an and Hadith is the holy book for Muslims as a way of life in everyday life. Qur'an itself consists of 30 juz, 114 letters and approximately 6,666 verses. While the Hadith is also very much making it difficult for Muslims who still lay preacher or a legal basis for the search for subjects interrelated among the verses in the Qur'an and Qur'anic verses linkages and Hadith. Today, existing search engines (Icon Find) but did not do a grouping of words that have been found so that the reader is difficult to understand because the scattered pages of documents. On the other hand people tend to have typing errors to look for a particular subject and if an error occurs writing the words that contain a particular subject was not found. Clerical errors are generally caused by the proximity of the keyboard layout, less adept at using finger, or because the two characters are located confused. Levenshtein algorithm is an algorithm that is reliable and can be used to calculate the relationship between the strings by way of calculating the distance or amount of difference between two strings. With this method the system is expected to have mistyped the recommendations and improvements to search and classify the subject of the search results in a separate sheet that allows the reader. Based on the experimental results generated that included the greater accuracy that the fewer the number of words recommended.Keywords— Search Engines, Writing Errors, Levenshtein algorithm, The Qur'an and Hadith digital.